Proteome Analysis Reveals Extensive Light Stress-Response Reprogramming in the Seagrass Zostera muelleri (Alismatales, Zosteraceae) Metabolism - Kumar, Manoj; Padula, Matthew P.; Davey, Peter; Pernice, Mathieu; Jiang, Zhijian; Sablok, Gaurav; Contreras-Porcia, Loretto; Ralph, Peter J. (Frontiers in Plant Science, 2017)
Seagrasses are marine ecosystem engineers that are currently declining in abundance at an alarming rate due to both natural and anthropogenic disturbances in ecological niches. Despite reports on the morphological and physiological adaptations of seagrasses to extreme environments, little is known of the molecular mechanisms underlying photo-acclimation and/or tolerance in these marine plants. This study applies the two-dimensional isoelectric focusing (2D-IEF) proteomics approach to identify photo-acclimation/tolerance proteins in the marine seagrass Zostera muelleri. For this, Z. muelleri was exposed for 10 days in laboratory mesocosms to saturation (control, 200 μmol photons m-2 s-1), supersaturation (SSL, 600 μmol photons m-2 s-1), and light limitation (LL, 20 μmol photons m-2 s-1). Using LC-MS/MS analysis, 93 and 40 protein spots were differentially regulated under SSL and LL conditions, respectively, when compared to the control. In contrast to the LL condition, Z. muelleri robustly tolerated super-saturation light than control conditions, evidenced by their higher relative electron transport rate and half-saturation of photosynthetic rate values. Proteomic analyses revealed up-regulation and/or appearances of proteins belonging to the Calvin-Benson and Krebs cycle, glycolysis, the glycine cleavage system of photorespiration, and the antioxidant system. These proteins, together with those from the inter-connected glutamate-proline-GABA pathway, shaped Z. muelleri photosynthesis and growth under super-saturation light conditions. In contrast, the LL condition negatively impacted the metabolic activities of Z. muelleri by down-regulating key metabolic enzymes for photosynthesis and the metabolism of carbohydrates and amino acids, which is consistent with the observation with lower photosynthetic performance under LL condition. This study provides novel insights into the underlying molecular photo-acclimation mechanisms in Z. muelleri, in addition to identifying protein-based biomarkers that could be used as early indicators to detect acute/chronic light stress in seagrasses to monitor seagrass health.